Exacerbation of symptoms of rheumatoid arthritis in the course of immunotherapy of non-small cell lung cancer - an analysis of medical cases and a review of the literature - Bargieł, Julia; Cabaj, Justyna; Chmielewska, Izabela; Wójcik-Superczyńska, Magdalena; Milanowski, Janusz (Journal of Education, Health and Sport, 2022)
Background: Lung cancer has been at the forefront of cancers with the highest incidence and mortality rates. Nowadays, there are available more effective forms of treatment such as immunotherapy. In the case of cancer cells expressing the PD-L1 receptor, pembrolizumab, atezolizumab and nivolmab are of particular use. While these drugs have the great benefit of stabilizing the disease, they are not without side effects, especially inflammatory changes in the joints. The aim of the study is to show the risk of immunotherapy in the form of exacerbation of inflammatory symptoms in patients with rheumatoid arthritis (RA) as a concomitant disease. Case report: Lung cancer (PD-L1 +) was diagnosed in three patients with a history of RA. After meeting the criteria of the drug program, the patients started molecularly targeted therapy with pembrolizumab and atezolizumab. The applied treatment brought a great benefit in the form of stabilization the neoplastic disease. Over time an exacerbation of inflammatory changes within the joints was noted, which significantly impeded everyday functioning in two patients. Due to this situation, immunotherapy was discontinued. Conlusions: Studies show that as many as 1/4 of patients treated with PD-L1 inhibitors experience side effects related to the autoimmune system. In the case of people suffering from RA, the use of immunotherapy may intensify inflammatory changes and increase pain, which significantly reduce the quality of life. Therefore, the risk of RA exacerbation as a side effect of biological therapy for lung cancer treatment should be popularized. This awareness will enable quick intervention and minimize the number of interrupted immunotherapies.